2010
DOI: 10.1007/s11814-010-0223-6
|View full text |Cite
|
Sign up to set email alerts
|

Coal flotation using a biosurfactant from Pseudomonas aeruginosa as a frother

Abstract: A biosurfactant-producing bacterial species (Pseudomonas aeruginosa) was grown in a mineral solution with gas oil as the source of carbon and energy. The biosurfactant was recovered from the solution by collecting the foam on the surface and drying. It had critical micelle concentration of 100 ppm. Froth characterization showed that the biosurfactant was superior to methyl isobutyl carbinol (MIBC) in terms of froth height and stability. The biosurfactant was examined in coal flotation as a frother. The combust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 14 publications
0
19
0
1
Order By: Relevance
“…The first investigation on using these biosurfactants in flotation of coal and minerals was done by Fazaelipoor et al [79]. They studied frothing characteristics and flotation applicability of rhamnolipid type biosurfactants as frother.…”
Section: Biofrothersmentioning
confidence: 99%
“…The first investigation on using these biosurfactants in flotation of coal and minerals was done by Fazaelipoor et al [79]. They studied frothing characteristics and flotation applicability of rhamnolipid type biosurfactants as frother.…”
Section: Biofrothersmentioning
confidence: 99%
“…frother height and half-life, in comparison with methyl isobutyl carbinol (MIBC). However, some points challenging the results reported by Fazaelipoor et al [13] are: 1) diesel oil being used as a biosurfactant solvent. After solvent evaporation, heavy hydrocarbon residuals of diesel oil would remain which increase the impurity of crude biosurfactant.…”
Section: Introductionmentioning
confidence: 91%
“…Although there are a number of studies related to the direct application of microorganisms in flotation and flocculation of minerals which are well reviewed by Hanumantha Rao et al [11] and Khoshdast and Sam [12], few scientific researches which apply biosurfactants have been found. The only available work on using rhamnolipid biosurfactants in flotation of coal and minerals was done by Fazaelipoor et al [13]. They studied frothing characteristics and flotation applicability of rhamnolipid type biosurfactants as a frother.…”
Section: Introductionmentioning
confidence: 99%
“…Fazaelipoor et al178 , a P. aeruginosa derived biosurfactant was examined in coal flotation as a frother; permitting a combustible matter recovery of 72-79 % with 10-15.5 % ash content supporting 55-57.5% separation efficiency. Recent studies showed that P. aeruginosa derived rhamnolipid exhibited better surface activity and frothability were studied when compared Page 22 of 46with conventional flotation frothers, methyl isobutyl carbinol, pine oil, Dowfroth-250 and Aerofroth-65 179.…”
mentioning
confidence: 99%